2007
DOI: 10.1504/ijemr.2007.014847
|View full text |Cite
|
Sign up to set email alerts
|

A classification of online bidders in a private value auction: evidence from eBay

Abstract: In traditional auctions, it is often assumed that bidders are a homogenous group. However, since most online bidders are average consumers instead of professional bidders, we suspect that online bidders are a heterogeneous group. The purpose of this paper is to explore the types of online bidders based on their real bidding behaviors in a popular auction site. A cluster analysis is employed and four types of online bidders are finally identified in a private value auction, namely, goal-driven bidders, experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…While there does appear to be considerable empirical research about on-line auction management, little of this research speaks directly to the charity organization's issues. For instance, Hou and Rego ( 2003 ) identified four types of bidders, namely, goal-driven bidders, experiential bidders, playful bidders, and opportunistic bidders. The opportunistic bidders on average pay the lowest price.…”
Section: Background Of Auctions In Virtual Spacementioning
confidence: 99%
“…While there does appear to be considerable empirical research about on-line auction management, little of this research speaks directly to the charity organization's issues. For instance, Hou and Rego ( 2003 ) identified four types of bidders, namely, goal-driven bidders, experiential bidders, playful bidders, and opportunistic bidders. The opportunistic bidders on average pay the lowest price.…”
Section: Background Of Auctions In Virtual Spacementioning
confidence: 99%
“…We consider a private-value auction where each bidder knows his valuation for the item, which is independent of others' valuations. The private-value setting has been supported by extensive literature that has empirically studied online auction platforms like eBay (Hou & Rego, 2007;Ockenfels & Roth, 2006;Roth & Ockenfels, 2002;Zeithammer, 2006). The seller has no intrinsic value for the good, and therefore, her reservation price is zero.…”
Section: Modelmentioning
confidence: 99%
“…The analysis revealed that there were certain bidding behaviors that appeared frequently in online auctions. Hou and Rego used hierarchical clustering to generate four distinct groups of bidding behaviors for standard eBay auctions, namely goal-driven bidders, experiential bidders, playful bidders, and opportunistic bidders [14]. They concluded that online bidders were a heterogeneous group rather than a homogenous one.…”
Section: Related Workmentioning
confidence: 99%
“…Bidder Feedback Rating (BFR) is useful in describing a bidder's experience level and established trustworthiness [8,14]. However, we should also notice the potential for fabricating feedback rating through collusion between misbehaving users and fraudulent bidding rings [2,4].…”
Section: User Attributesmentioning
confidence: 99%